Profitability analysis of pilot plant utilizing waste cassava peels and pulp as substitute for maiz in in animal feed formulation (Journal of Science and Technology, 2016)
The Government of the Republic of Ghana has initiated a major revolution in the cassava starch, salt, oil palm and cotton industries. These are industrial raw materials bases for many commercial products. Cassava starch is the base material for production of over 2,000 kinds of products, for example, starch syrup, grape sugar, foodstuffs, modified starch, medicaments, cosmetics, shoe polish, dry battery and chemicals for floatation. It is estimated that 2 million tonne of cassava crop will be produced over the next ten years, yielding about 480,000 tonne of cassava starch and about 640,000 tonne of cassava peels. The cassava starch revenue is projected at about US$96 million annually. Cassava starch and peel constitute approximately 22.5% and 1.4% of the cassava tuber, respectively. The reported composition of fresh cassava peels are moisture (25-30%), fiber (50-60%), starch (4-5%), protein (0.7%) and sugars (2.0%). Maize bran constitutes between 25 and 40% of the feed in pigs, rabbits, poultry and sheep formulations. The cassava pulp constitutes about 8.6% of the cassava tuber and it is a large source of carbohydrate and fiber for animal feed. With the expressed interest in the cassava starch, the technical problem is the utilization of the cassava peel and cassava meal by-products. The utilization of the by-products in animal feed formulation for replacing substantial amounts of maize is the subject of this paper. Further the financial and economic feasibility of a pilot plant production of animal feed was established. The project is financially feasible at capacities greater than 60% of installed plant capacity. The liquidity ratios were; current ratio 2:1, quick ratio 1:1 and debt ratio less than 0.5.